Use Tableau prep to make workflow documentation easier - Allchin, Carl (O'Reilly Media, Inc., [2024], 2024)
Tableau is one of today's most powerful business intelligence analytics and data visualization tools. It empowers people across the organization to see and understand data for better business decision-making. These Shortcuts will provide you with simple tips and tricks for creating charts, dashboards, and stories that turn data into actionable insights.
Keywords: Tableau (Computer file); Information visualization -- Computer programs; Visual analytics -- Data processing; Visualisation de l'information; Logiciels; Analyse visuelle; Informatique